A STUDY ONEMPLOYABILITY SKILLSOF THE MANAGEMENT GRADUATES IN CHENNAI CITY - UNNIKRISHNAN, SHRUTHI; M, SANGEETHA.; MAGESWARI. T, UMA (International Journal of Psychosocial Rehabilitation, 2020)
Employability has been defined as "capability to urge and maintain satisfactory work." All the tutorial institution consider employability skills in management education to be a serious challenge. Management education is concentrated on developing a good array of management knowledge and skills. More emphasis is placed on the candidates 'performance at the work and this needs a group of skills that match the work. Students are required to fine-tune their team-building and communication skills additionally to the subject-specific job. This paper sheds light on the prevailing research results and practices of employability skills and presents a review on aspects like employability definitions, employability skills, employer needs and expectations harmonizing employer needs and therefore the nature of employability. India witnessed a huge change in its educational system within the 21st century. Many of the management institutions are still following the normal method of teaching; the necessity of hour is to bridge the gap between academia and industry. Management education in INDIA isn't very old; after the establishment of the IITs, there was dire need for similar establishments within the field of management education. a group of attribute and knowledge that each one of the labor market participants should possess to make sure they need the potential of being effective within the workplace—to the advantage of themselves, their employer and wider economy”.